Hubungan Pengetahuan Dan Sikap Ibu Balita Dengan Kejadian Ikutan Pasca Imunisasi Di Pusat Kesehatan Masyarakat Oebobo Tahun 2016 - Ririn Widyastuti (JURNAL INFO KESEHATAN, 2017)
Immunization is very important to prevent the occurrence of certain diseases in a person, a group of people (population) or even eliminate certain diseases in the world. The immunization program that has been running for a long time in Indonesia, has recently been hampered by the spread of incorrect information about immunization so that many parents are hesitant and afraid to immunize their babies. Incorrect information often uses fear (fear mongering) issues to post-immunization events that may occur in children after getting immunized. Post-Immunization Events or Adverse Events Following Immunization (AEFI) is a medical event that is suspected to be related to immunization, either in the form of vaccine reactions or adverse effects, pharmacological effects, injection reactions or procedural errors. Problem formulation in this study is how is the relationship between the knowledge and attitudes of the mother of a toddler and the post-immunization incident at the Oebobo Public Health Center in 2016? Research Objectives to determine the relationship between knowledge and attitudes of the under-fives with the Post-Immunization Occurrence at the Oebobo Public Health Center 2016. The type of research used was an analytic survey research using a cross-sectional research design. The population in this study were all mothers of children under five (0-59 months) in the Oebobo Public Health Center work area, amounting to 348 people. The sampling technique was accidental sampling that met the inclusion and exclusion criteria of 80 people. Data collection techniques using questionnaires. Data analysis technique uses univariate analysis in the form of frequency distribution and bivariate tables with Chi-Square. The results of the study are presented in the form of frequency distribution of children affected by post-immunization events 52 people (65%) with mild reactions of 45 cases (86.5%). Respondents' knowledge about Post-Immunization Accident is good 29 respondents (36.25%). Positive attitudes of mothers under five are 68 respondents (85%). There is a relationship between the knowledge of mothers under five with Post-Immunization Events (p-value: 0.038) and there is no relationship between the attitudes of mothers under five with Post-Immunization Events (p-value: 0.744). Conclusion: There is a relationship between the knowledge and attitudes of mothers of under-fives with the Post-Immunization Accident at Oebobo Public Health Center 2016.